Penerapan E-Commerce bagi UMKM sebagai Pemasaran Digital dalam Menghadapi Revolusi Industri 4.0 (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
The development of digital technology and the Industrial Revolution 4.0 have driven significant changes in marketing activities, including for Micro, Small, and Medium Enterprises (MSMEs). The use of e-commerce has become an important digital marketing strategy for MSMEs to increase competitiveness and business revenue. This study aims to examine the role of e-commerce implementation as a digital marketing tool for MSMEs in facing the Industrial Revolution 4.0 and analyze its impact on increasing MSME revenue and competitive advantage. The research method used is a qualitative descriptive approach with data collection techniques through literature studies of various literature sources such as books, scientific journals, and online publications relevant to the research topic. The results of the study indicate that the implementation of e-commerce has a positive impact on MSMEs, including expanding market reach, increasing marketing efficiency, and driving increased business revenue. In addition, e-commerce also plays a role in increasing MSME competitive advantage through product innovation, improving service quality, and strengthening relationships with consumers. However, the implementation of e-commerce in MSMEs still faces several challenges, such as low digital literacy, limited human resources, and minimal technical assistance. Therefore, ongoing support from various parties is needed so that the use of e-commerce by MSMEs can run optimally and sustainably in the digital era.